COVID-19 infections in staff of an emergency care hospital after the first wave of the pandemic in Germany - Stüven, Philipp; Mühlenbruch, Georg; Evenschor-Ascheid, Agnes; Conzen, Ellen; Peters, Claudia; Schablon, Anja; Nienhaus, Albert (German Medical Science GMS Publishing House, 2022)
Background: Hospital staff have an increased risk of SARS-CoV-2 infection. It is thus necessary to monitor the situation because infected staff may in turn infect patients and their family members. Following the first wave of infection in the summer of 2020, the Rhine-Maas Hospital (RMK) provided all staff the opportunity to be tested for SARS-COV-2 via antibody testing. Methods: The tests were carried out from 19.6.2020 to 17.7.2020. The IgG antibody test qualitatively tested for SARS-CoV-2 antibodies via enzyme-linked immunosorbent assay (ELISA). An IgG titre of 0.8 IU/mL or more was considered positive. All staff who tested positive for SARS-CoV-2 by PCR testing after February 2020 were also included in the study. Occupational and non-occupational risk factors for infection were determined. Staff in the intensive care ward, the emergency depart-ment, or a SARS-CoV-2 ward ("corona ward") were predefined as having increased exposure. Odds ratios (OR) were calculated using logistical regression for occupational and private infection risk.Results: 903 staff members (58.9%) with complete data took part in the cross-sectional study. 52 staff members (5.8%) had a positive PCR test result in their medical history or tested positive in the IgG test. Around half of the infections (55%) were only detected by serological testing during the study. Staff with tasks classified as at-risk had an OR of 1.9 (95% CI 1.04-3.5) for infection. Risk factors also included private contacts to people infected with SARS-CoV-2 and holidays in risk areas. At the time of data collection, 11.5% of those with the disease reported that they had not yet fully recovered from COVID-19.Discussion: Following the first COVID-19 wave, 5.3% of staff at the RMK were infected. An increase in occupational infection risk was found even after controlling for non-occupational infection risks. This should be taken into account with regard to the recognition of COVID-19 as an occupational disease. Methods to improve protection against nosocomial transmissions should be considered.